(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The reliability of foundations constructed on collapsible loess soils remains one of the most complex problems in geotechnical engineering because such soils may appear sufficiently strong in their natural dry or low-moisture state but experience sudden structural breakdown, volume reduction and differential settlement after wetting. This article investigates a performance-based approach to shallow and deep foundation design on collapsible loess deposits under the combined influence of seasonal moisture variation, irrigation leakage, accidental water infiltration and seismic loading. The research is based on analytical interpretation of published geotechnical studies, comparative assessment of international design principles, and a conceptual engineering model that links soil collapsibility, foundation stiffness, allowable settlement, drainage reliability and structural serviceability. The study demonstrates that traditional bearing-capacity-oriented design is not sufficient for loessial ground because the decisive limit state is often not ultimate failure but wetting-induced deformation, tilting and loss of operational performance. The article argues that foundation design on collapsible soils should include staged site investigation, laboratory collapse-potential testing, assessment of hydrogeological risk, control of surface and subsurface water, improvement of weak loess layers where necessary, and selection of foundation systems according to predicted deformation rather than only calculated bearing resistance. The results indicate that the most rational solutions are obtained when shallow foundations are combined with soil replacement, compaction or stabilization for lightly loaded buildings, while pile foundations, rigid rafts or combined pile-raft systems become preferable where collapsible layers are thick, water exposure is probable, or seismic demand is significant. The article concludes that a performance-based framework can reduce differential settlement risk, improve long-term serviceability and provide a scientifically grounded basis for foundation decisions in regions where loess soils, irrigation networks and seismicity interact.